2018
DOI: 10.1016/j.jvs.2017.11.098
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral embolic protection in thoracic endovascular aortic repair

Abstract: The use of a CEPD with TEVAR appeared to be safe and feasible in this first pilot study and could serve as a useful adjunct to reduce cerebral injury. The significance of gaseous embolization and its role in cerebral injury in TEVAR warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 30 publications
0
29
0
3
Order By: Relevance
“…6 These filters do not protect against gaseous embolism, and even with bilateral use in the carotid arteries, the posterior cerebral circulation remains unprotected and prone to embolization. 15 Clearly, effective, procedure-specific techniques that provide global CEP during TEVAR are required; our endeavor in the present case was to fill this void and improve the safety of such procedures in patients at high-risk for embolization. Being an unfamiliar and complex procedure requiring multidisciplinary collaboration, we had to proceed in an unhurried and methodical manner, using multiple neuromonitoring modalities, which resulted in a fairly long procedure.…”
Section: Discussionmentioning
confidence: 99%
“…6 These filters do not protect against gaseous embolism, and even with bilateral use in the carotid arteries, the posterior cerebral circulation remains unprotected and prone to embolization. 15 Clearly, effective, procedure-specific techniques that provide global CEP during TEVAR are required; our endeavor in the present case was to fill this void and improve the safety of such procedures in patients at high-risk for embolization. Being an unfamiliar and complex procedure requiring multidisciplinary collaboration, we had to proceed in an unhurried and methodical manner, using multiple neuromonitoring modalities, which resulted in a fairly long procedure.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recent in vitro studies demonstrated air release from angiographic catheters and during deployment of different TEVAR devices, with a potential risk for air embolization in the supra-aortic arteries. [7][8][9] Grover et al 10 showed in vivo that 90% of MES in MCA during TEVAR are caused by air emboli, and the highest number was measured during stentgraft deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly widespread application of transcatheter aortic valve replacement (TAVR) has encouraged the development and implementation of cerebral protection devices for prevention of intra-operative stroke. The Sentinel Cerebral Protection System (Claret Medical, Santa Rosa, CA) is currently the only FDA-approved cerebral protection device for TAVR, and preliminary data regarding its efficacy in both TAVR [4] and TEVAR of the descending aorta [5] have been promising. Here we present the first published report of cerebral protection device utilization during TEVAR for an ascending aortic aneurysm.…”
Section: Introductionmentioning
confidence: 99%